Primerjava vadbe ravnotežja v vodi in na kopnem ter vpliv na odrivno moč - Sašek, Matic (Šport (Ljubljana), 2020)
Aquatic exercises represent safer alternative to land exercise considering balance training. But hydrodynamic laws in water cause human body to work differently as on land. Those adaptations could affect balance training prosperity. The aim of this study was to compare land-based versus water-based balance training and to evaluate effects of wobble board exercise on static and dynamic balance and jumping ability. Thirty-one participants were divided in three groups; land-based (KOP), water-based (VOD) and control (KON). Before and after 7-weeks of wobble board exercise single leg stance body sway parameters (static balance), y-test (dynamic balance), squat jump and countermovement jump (jumping ability) were measured. We used ANCOVA to analyse the results. Significant group x time results were found for counter movement jump (p=0,029). Post hoc test showed significant differences between KOP and KON while differences between VOD and KON showed tendency towards VOD. We found no effects of exercise on static and dynamic balance although we found some differences inside groups before and after exercise in KOP and VOD for dynamic balance. We assume wobble board exercise is effective method for improving jumping ability and consequently stiffness of joints. Since we found no differences between land-based and water-based exercise both environments can be used for training.
Keywords: aquatic exercises; balance; ravnotežje; ravnotežne deske; vadba; voda; water; wobble boards